Extraction and some characteristics of mango seed kernel starch for industrial applications / Saidu Hassan Musa and Balarabe Sarki Sagagi - Musa, Saidu Hassan; Sagagi, Balarabe Sarki (Faculty of Applied Sciences, 2023)
Starch is extensively used for various applications in many industries such as food, pharmaceutical, textile, and many more. Mango starch is a better solution to reduce the reliance on food crops starch for food security. Starch is a polymer of hexa carbon monosaccharide-D-glucose. It is highly abundant in corn seeds, potato tubers, and the roots and stems of other plants. All green plants make and store D- glucose in the form of spherical starch granules: 2-100 μm in diameter. Most commercially available starches are isolated from grains such as maize, rice, and wheat and from tubers such as cassava and potato. A novel starch from mango seed was extracted and characterized using a standard method for potential industrial applications. A high yield of 76.82 % and further characterized through Proximate analysis, with a moisture content of 4.790, ash content of 0.210, the starch protein content of 0.043, and starch lipid 0.380. FTIR, morphological structures, and some physical characteristics such as water binding capacity (WBC), solubility, and other parameters were observed for their suitability in industrial applications.